On the hysteresis phenomenon during flow boiling heat transfer on a hydrophilic carbon/carbon surface. (October 2020) - Doretti, Luca; Righetti, Giulia; Longo, Giovanni A.; Zilio, Claudio; Mancin, Simone
Abstract: This paper presents a detailed discussion on the hysteresis phenomenon caught during the flow boiling heat transfer of R245fa on a Carbon/Carbon surface. Due to the partial hydrophilicity of the Carbon/Carbon surface, a hysteresis in flow boiling heat transfer is observed and studied to understand the underlining heat transfer mechanisms on the basis of the surface activation. A combined experimental approach is developed by monitoring the local wall temperature and contemporarily recording the two-phase flow patterns using a high-speed video camera. The observed dewetting/rewetting phenomenon is linked to the activation process of the Carbon/Carbon surfaces giving new insights on the boiling behavior of hydrophilic surfaces. The results show that after activation the heat transfer coefficients increases up to 20%. The experimental results are compared against the estimations of a model recently proposed by the present Authors and based on R134a measurements. The proposed model is able to predict the heat transfer coefficients within ±20%. Highlights: R245fa flow boiling on a Carbon/Carbon surface is studied. A hysteresis of boiling heat transfer is observed and studied. A combined experimental methodology is applied to study the surface activation process. The dewetting/rewetting phenomenon during flow boiling was linked to the activation process.